ISLAMIC FINANCE-ECONOMIC GROWTH NEXUS IN BANGLADESH: AN ARDL APPROACH - Chowdhury, Nazreen Tabssum; Abduh, Muhamad (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2012)
Unlike previous banking system, today there are several Islamic Banks are operating by offering various kinds of Islamic products in the world. Some countries introduced Islamic Banking system earlier than others but the products and the services which are offered by Islamic Banks are slightly different from one country to another. Islamic banks have been operating in Bangladesh from last three decades together with the conventional banks. This research aimed to examine the relationship between Islamic banking developments to the country’s growth from evidence of Bangladesh. By looking at the relationship tried to examine the nature of the relationship long run effects on economy. The research questions were “does Islamic banks in Bangladesh contribute in country's economic growth by increasing performance? And what kind of relationship exists between Islamic banks development and Bangladesh's economic growth?”. Quarterly data were used from the period of Q1:2004 to Q2:2011.Auto Regressive Distributed Lag (ARDL) bound testing technique for cointegration was applied to estimate the long run relationship. A long run relationship was found between Islamic financing and economic growth which shows demand following relationship.